Observation and simulation of evapotranspiration partitioning under wet and dry canopy conditions in a boreal forest of eastern Canada - Hadiwijaya, Bram (Université Laval, 2021)
Boreal forests account for around a third of the world's forest biomes and occupy the second largest vegetated area after tropical forests. Given its large geographical distribution, the boreal forest regulates water fluxes over vast areas and thus impacts climatology and hydrology at regional and global scales. Understanding the interactions between this ecosystem and the atmosphere is therefore crucial. Many studies have investigated the evapotranspiration of boreal forests, but only a handful have focused on the dynamics of evapotranspiration partitioning into overstory transpiration, wet canopy evaporation, and understory evapotranspiration on a fine temporal scale. The main objective of this thesis is to analyze the dynamics of evapotranspiration partitioning, particularly overstory transpiration and wet canopy evaporation in a humid boreal forest of eastern Canada. The approach is based on field observations and model outputs from the Canadian Land Surface Scheme (CLASS, run in offline mode), at the Montmorency Forest (47°17′18″N; 71°10′05.4″W) of Université Laval, Québec, Canada. This site is classified as a humid boreal forest with an aridity index of 0.57 and mean annual precipitation of 1583 mm (60% rain, 40% snow). This region is under the influence of a continental subarctic climate (Köppen classification Dfc), with a mean annual temperature of 0.5℃ and the growing season stretching from June to October. The experimental setup consists of two sites with balsam fir stands at different levels of maturity (Juvenile and Sapling), both equipped with eddy covariance flux tower. The more mature stand at the Juvenile site has a higher mean leaf area index (3.6) than the Sapling site (2.9). The evapotranspiration of the balsam fir stands was monitored by an eddy covariance system installed on the flux tower whereas the overstory transpiration and canopy water balance were measured inside three 400-m² plots located in the vicinity of each flux tower. The analysis focuses on the 2017 and 2018 growing seasons. ...